Importance of Initial Interfacial Steps during Chalcopyrite Bioleaching by a Thermoacidophilic Archaeon - Safar, Camila (2020)
Studies of thermophilic microorganisms have shown that they have a considerable biotechnological potential due to their optimum growth and metabolism at high temperatures. Thermophilic archaea have unique characteristics with important biotechnological applications; many of these species could be used in bioleaching processes to recover valuable metals from mineral ores. Particularly, bioleaching at high temperatures using thermoacidophilic microorganisms can greatly improve metal solubilization from refractory mineral species such as chalcopyrite (CuFeS2), one of the most abundant and widespread copper-bearing minerals. Interfacial processes such as early cell adhesion, biofilm development, and the formation of passive layers on the mineral surface play important roles in the initial steps of bioleaching processes. The present work focused on the investigation of different bioleaching conditions using the thermoacidophilic archaeon Acidianus copahuensis DSM 29038 to elucidate which steps are pivotal during the chalcopyrite bioleaching. Fluorescent in situ hybridization (FISH) and confocal laser scanning microscopy (CLSM) were used to visualize the microorganism–mineral interaction. Results showed that up to 85% of copper recovery from chalcopyrite could be achieved using A. copahuensis. Improvements in these yields are intimately related to an early contact between cells and the mineral surface. On the other hand, surface coverage by inactivated cells as well as precipitates significantly reduced copper recoveries.